2020
DOI: 10.1039/d0nr02177f
|View full text |Cite
|
Sign up to set email alerts
|

Multi-component (Ag–Au–Cu–Pd–Pt) alloy nanoparticle-decorated p-type 2D-molybdenum disulfide (MoS2) for enhanced hydrogen sensing

Abstract: The nanoscale interface between multi-component (Ag–Au–Cu–Pd–Pt) alloy nanoparticles on MoS2 sheets increase its work function making an ohmic contact into Schottky with gold electrodes. This drastically enhances response towards hydrogen gas.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 46 publications
(46 reference statements)
1
39
0
Order By: Relevance
“…Dealloying strategy has been used for the preparation of many nano‐porous catalysts [74–77] . Qiu et al .…”
Section: Synthesis Of Nanosized Heasmentioning
confidence: 99%
“…Dealloying strategy has been used for the preparation of many nano‐porous catalysts [74–77] . Qiu et al .…”
Section: Synthesis Of Nanosized Heasmentioning
confidence: 99%
“…HEA has been explored in various electrochemical activities as CO2 reduction 23 , for OER 6 , for HER 24 (hydrogen evolution reaction) due to its unique properties 25 . Our previous studies have found AgAuPtPdCu alloys having exceptional electrochemical catalyst properties [26][27][28] .…”
Section: Introductionmentioning
confidence: 95%
“…Till now, HEA has been explored in various electrochemical activities as CO2 reduction 23 , for OER 6 , for HER 24 (hydrogen evolution reaction) due to its unique properties 25 . Our previous studies have found AgAuPtPdCu alloys having exceptional electrochemical catalyst properties [26][27][28] .…”
Section: Introductionmentioning
confidence: 95%